Fossil Pollen and Insect Evidence for Postglacial Environmental Conditions, Nushagak and Holitna Lowland Regions, Southwest Alaska - Short, Susan K.; Elias, Scott A.; Waythomas, Christopher F.; Williams, Nancy E. (ARCTIC, 1992)
This paper discusses the results of pollen and insect analyses of postglacial samples from the Nushagak and Holitna lowlands, southwest Alaska. Although radiocarbon dating control is poor, the samples can be arranged in a relative-age sequence based on stratigraphic occurrence. The fossil pollen data record the regional transition from a late-glacial dry graminoid tundra through the postglacial Birch, Alder, and Spruce zones. The lack of xeric insect species in the early postglacial suggests that the lowlands of southwest Alaska experienced maritime climatic conditions, in contrast to the interior. Rapid climatic warming is subsequently indicated by the fossil insect data, although the arrival of alder in the region postdates 8500 yr BP. There is no evidence for coniferous forest in the Nushagak lowland at any time in the postglacial, although spruce arrived in the Holitna lowland in the mid-postglacial.Key words: pollen analysis, fossil insects, paleoenvironments, postglacial, southwest Alaska RÉSUMÉ. Cet article traite des résultats d’analyses polliniques et d’insectes d’échantillons postglaciaires venant des basses-terres de Nushagak et d’Holitna, dans le sud-ouest de l’Alaska. Bien que le contrôle de la datation par le radiocarbone soit médiocre, les échantillons peuvent être classés en ordre d’âger elatif, d’après leur occurrence stratigraphique. Les données de pollens fossiles traduisent le passage de la région d’une toundra sèche de graminées datant de la fin de l’époque glaciaire, à des zones postglaciaires de bouleaux, d’aulnes et d’épicéas. L’absence d’espèces d’insectes xérophiles au début du postglaciaire donne à penser que les basses-terres du sud-ouest de l’Alaska ont connu des conditions climatiques maritimes, contrairement à l’intérieur. Les données sur les insectes fossiles permettent donc d’établir qu’il y a eu un réchauffement climatique rapide, bien que l’arrivée de l’aulne dans la région soit postérieure à 8500 ans avant le présent. On n’a pas de preuve de l’existence d’une forêt de ...